Implementasi Prinsip Negara Hukum dalam Meningkatkan Good Governance di Indonesia - Yuliansa, Dobi; Helandri, Joni; Sahary, Athika Nur Aulia; Pusfitasari, Yuni; Artika, Hodijah (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
The principle of the rule of law has been widely recognized as a crucial foundation for good governance and social justice in Indonesia. However, its implementation still faces various challenges that affect its effectiveness in improving good governance. This research aims to investigate the implementation of the rule of law principle in enhancing good governance in Indonesia. The methodology used is a qualitative approach with a literature review involving analysis of various related literature and documents. The research findings indicate that the rule of law principle plays a significant role in building good governance, yet it is confronted with challenges such as weak institutional capacity, legal uncertainty, and limited community participation. The conclusion of this research underscores the need for sustained efforts to strengthen institutional capacity, promote community participation, and overcome cultural and political barriers in realizing an effective rule of law principle to enhance good governance in Indonesia.